Knee joint impedance hybrid modeling and control of Functional Electrical Stimulation (FES)-cyclingfor paraplegic: free swinging trajectory - Ahmad, M. K. I.; Ibrahim, B. S. K. K.; Rahman, K. A. A.; Masdar, A.; Nasir, N. H. M.; Abdul Jamil, Mahadi (2012)
Functional electrical stimulation (FES) has been used to restore the function of paralyzed muscles due to spinal cord injury (SCI). FES induced movement control is a significantly challenging area due to complexity and nonlinearity of musculoskeletal system. A crucial issue of FES is the control of motor function by the artificial activation of paralyzed muscles due to the various characteristics of the underlying physiological/biomechanical system. Muscle response characteristics are nonlinear and time-varying with fatigue issues. In this approach only the quadriceps muscle is stimulated to perform the trajectory motion. This paper presents the initial development of control strategies using FLC and GA in order to optimize the system by FEScycling trajectory control via Analog Digital Converter,ADC.